Estrogen Receptor Beta Prevents Signet Ring Cell Gastric Carcinoma Progression in Young Patients by Inhibiting Pseudopodia Formation via the mTOR–Arpc1b/EVL Signaling Pathway - Wang, Xingzhou; Xia, Xuefeng; Xu, En; Yang, Zhi; Shen, Xiaofei; Du, Shangce; Chen, Xiaotong; Lu, Xiaofeng; Jin, Wei; Guan, Wenxian (Frontiers in Cell and Developmental Biology, 2021)
Signet ring cell gastric carcinoma (SRCGC) is a poorly differentiated malignancy, and can be highly dangerous in the progression stage. There is a higher male to female ratio among patients with signet ring cell carcinoma as compared to patients with non-SRCGC. Here, we studied estrogen receptor beta (ERβ) to explore the role of sex-associated factors in SRCGC. We analyzed the clinicopathological statistics of patients with SRCGC, and conducted a series of in vitro experiments. Immunohistochemistry showed that patients with low ERβ expression were at risk of poor prognosis and higher T stage. In vitro assays indicated that ERβ might prevent SRCGC progression by inhibiting cell proliferation and invasiveness and by promoting anoikis. Western blotting and quantitative RT-PCR proved that the mTOR–Arpc1b/EVL signaling pathway might participate in the negative regulatory role of ERβ. In conclusion, our findings show that ERβ might inhibit the malignancy of signet ring cells in patients with SRCGC, indicating that ERβ might be a potential target in adjuvant treatment.